2022
DOI: 10.1126/science.abq3773
|View full text |Cite
|
Sign up to set email alerts
|

Broadly neutralizing antibodies target the coronavirus fusion peptide

Abstract: The potential for future coronavirus outbreaks highlights the need to broadly target this group of pathogens. We use an epitope-agnostic approach to identify six monoclonal antibodies that bind to spike proteins from all seven human-infecting coronaviruses. All six antibodies target the conserved fusion peptide region adjacent to the S2' cleavage site. COV44-62 and COV44-79 broadly neutralize alpha and beta coronaviruses, including SARS-CoV-2 Omicron subvariants BA.2 and BA.4/5, albeit with lower potency than … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
173
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(203 citation statements)
references
References 75 publications
12
173
1
Order By: Relevance
“…Apart from the SH region mentioned earlier, S2 FPs are also highly conserved among all coronavirus genera, suggesting that broad-spectrum antibodies could be found by targeting this epitope 86 88 . Some recently identified antibodies to this epitope have excellent broadly neutralizing activity against alpha-CoVs, beta-CoVs and even some gamma-CoVs and delta-CoVs 86 , 87 . For example, COV44-62 and COV44-79, which were both isolated from patients recovering from COVID-19, can bind the S2 FP region through recognition of the ‘RSFIEDLLF’ motif.…”
Section: The S2 Fpsmentioning
confidence: 80%
See 2 more Smart Citations
“…Apart from the SH region mentioned earlier, S2 FPs are also highly conserved among all coronavirus genera, suggesting that broad-spectrum antibodies could be found by targeting this epitope 86 88 . Some recently identified antibodies to this epitope have excellent broadly neutralizing activity against alpha-CoVs, beta-CoVs and even some gamma-CoVs and delta-CoVs 86 , 87 . For example, COV44-62 and COV44-79, which were both isolated from patients recovering from COVID-19, can bind the S2 FP region through recognition of the ‘RSFIEDLLF’ motif.…”
Section: The S2 Fpsmentioning
confidence: 80%
“…For example, COV44-62 and COV44-79, which were both isolated from patients recovering from COVID-19, can bind the S2 FP region through recognition of the ‘RSFIEDLLF’ motif. Interestingly, these antibodies do not compete with S2P6, the aforementioned S2 SH-targeting antibody, for binding to the SARS-CoV-2 S protein 86 , suggesting the possibility of combining S2 SH and S2 FP recognition in a bispecific antibody. Crystal structure analysis revealed that COV44-62 interacts with S2, that spans residues 814–824, mainly through hydrogen bonds, salt bridges and hydrophobic interactions within HCDR1, HCDR2, HCDR3, LCDR1 and LCDR3.…”
Section: The S2 Fpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibodies targeting the fusion peptide could block either protease cleavage or insertion of cleaved fusion peptide into host membrane. Interestingly, recent studies have revealed that some antibodies do indeed target the fusion peptide and contribute to SARS‐CoV‐2 neutralization 242,243,248 …”
Section: Neutralizing Epitopes On Sars‐cov‐2 Spikementioning
confidence: 99%
“…These broad sarbecovirus SARS-CoV-2 NAbs (bsNAbs) have epitopes located on sarbecovirus conserved regions, and people believe that they would not be easily escaped by SARS-CoV-2 variants. Various bsNAbs targeting spike protein's RBD or S2 region have been discovered [24][25][26][27] . S2-targeting bsNAbs indeed displayed exceptional SARS-CoV-2 neutralization breadth, but their potency is rather low for NAb drug development.…”
Section: Mainmentioning
confidence: 99%